How DFID can better manage complexity in development programming - Sharp, Samuel; Valters, Craig; Whitty, Brendan (ODI, 2019)
The United Kingdom’s (UK) Department for International Development (DF ID) is an ambitious government department that is committed to reducin g poverty and conflict overseas. Many of the issues on which DFID work s are complex; whether focused on climate change, gender equality, hea lth or other priorities, simple solutions rarely exist. And to tackle these complex challenges, DFID staff must interact with unpredictable systems of political, organisational and individual behaviours and inc entives. There is a risk that complex problems spur more complicated p rogrammes; that the complexity of development challenges is addressed through designing programmes with too many projects and implementers. While there may be valid reasons for this, too many of these complicat ed programmes will overburden staff. This briefing note is the outcome of an ongoing process within DFID to confront these issues and answer the question: how can DFID design and manage programmes to address co mplex development challenges without creating too much staff workload? Key messages DFID deals with complex problems, which require flexible systems to support testing, learning and adaptation. • Complex proble ms do not necessarily require workload-heavy delivery structures, but simpler approaches depend on delivery partners’ experience and compete nce. • However, programmes that tackle complex problems do require mor e hands-on engagement and face more workload from inflexible complianc e requirements. We suggest that DFID and similar agencies: • Pay close r attention to delivery options in programme design, making use of exi sting options where possible and, where not, fostering local organisat ions through long-term investments. • Encourage programme designers to articulate how ambition matches resources and consider ‘good enough’ design. • Reduce the burden of compliance by cultivating partner auton omy, reassessing results and valuefor-money requirements and promoting more flexible contracting and procurement. • Plan and prioritise mana gement resources across a portfolio of programmes to make sure they ca n be focused in the right areas, where the complexity of the problem r equires greater engagement.